Cover, Content, and Editorial Note from Borneo J Pharm Vol. 8 No. 4 November 2025: Bridging Natural Potential, Clinical Evidence, and Regulatory Frameworks - Chief Editor of Borneo J Pharm (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Assalamu’alaikum Wr. Wb. Alhamdulillahirabbil ‘alamin. The next edition of Borneo Journal of Pharmacy (Borneo J Pharm) has been published in November 2025. This edition contains ten articles: Pharmacology-Toxicology, Pharmacognosy-Phytochemistry, Pharmaceutical, Analytical Pharmacy-Medicinal Chemistry, Microbiology Pharmacy, Natural Product Development, Management Pharmacy, and Pharmaceutical Regulations. This edition includes writings from three countries: Australia, Indonesia, and Thailand. The authors come from several institutions, including Universitas Halu Oleo, Thammasat University, Politeknik Bina Husada Kendari, Universitas Mulawarman, Sekolah Tinggi Ilmu Kesehatan Buleleng, Universitas Hasanuddin, Universitas Mandala Waluya, Universitas Hang Tuah, Akademi Farmasi Surabaya, Universitas Bakti Tunas Husada, Universitas Muhammadiyah Banjarmasin, Institut Teknologi Bandung, Monash University, Universitas Muhammadiyah Surakarta, Universitas Airlangga, Universitas Lambung Mangkurat, Universitas Muhammadiyah Magelang, Khon Kaen University, Universitas Indonesia, and Indonesian Food and Drug Authority. This edition underscores the multi-faceted nature of pharmaceutical sciences in Indonesia, featuring research that spans the